2018
DOI: 10.1039/c8cp02422g
|View full text |Cite
|
Sign up to set email alerts
|

Oxyhydroxide of metallic nanowires in a molecular H2O and H2O2 environment and their effects on mechanical properties

Abstract: To avoid unexpected environmental mechanical failure, there is a strong need to fully understand the details of the oxidation process and intrinsic mechanical properties of reactive metallic iron (Fe) nanowires (NWs) under various aqueous reactive environmental conditions. Herein, we employed ReaxFF reactive molecular dynamics (MD) simulations to elucidate the oxidation of Fe NWs exposed to molecular water (H2O) and hydrogen peroxide (H2O2) environment, and the influence of the oxide shell layer on the tensile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 59 publications
(230 reference statements)
0
30
0
Order By: Relevance
“…Previous theoretical studies indicated that plastic deformation always starts mechanically through emission of initial dislocations from the free surface, oxide shell layer, and/or the interface of the NW for the pristine and oxide-coated NWs that affect the overall mechanical properties. 2,23,31 However, it is difficult to identify exactly the location of initiation of initial dislocations. Generally, initial dislocation sources activated from these sites to initiate plastic deformation is associated with the combined effects of the geometry, the presence of local defects, the local atomic structure, the thickness of the oxide shell layer, the interface, surface morphologies, the size of the NW, and the applied strain rate.…”
Section: B Size-dependent Mechanical Properties Analyzed By Using Comentioning
confidence: 99%
See 1 more Smart Citation
“…Previous theoretical studies indicated that plastic deformation always starts mechanically through emission of initial dislocations from the free surface, oxide shell layer, and/or the interface of the NW for the pristine and oxide-coated NWs that affect the overall mechanical properties. 2,23,31 However, it is difficult to identify exactly the location of initiation of initial dislocations. Generally, initial dislocation sources activated from these sites to initiate plastic deformation is associated with the combined effects of the geometry, the presence of local defects, the local atomic structure, the thickness of the oxide shell layer, the interface, surface morphologies, the size of the NW, and the applied strain rate.…”
Section: B Size-dependent Mechanical Properties Analyzed By Using Comentioning
confidence: 99%
“…Generally, initial dislocation sources activated from these sites to initiate plastic deformation is associated with the combined effects of the geometry, the presence of local defects, the local atomic structure, the thickness of the oxide shell layer, the interface, surface morphologies, the size of the NW, and the applied strain rate. 2,21,22,31 Therefore, the basic driving force for size-dependent mechanical deformation is believed to arise from the free surface, the oxide region, and/or the interface. Therefore, the low yield strength value of the oxide-coated NWs compared to their pristine counterparts and the softening as a function of diameter can be explained by the local structural analysis at the vicinity of oxide region and the free surface of NWs.…”
Section: B Size-dependent Mechanical Properties Analyzed By Using Comentioning
confidence: 99%
“…There are several ReaxFF studies on metal oxidation with water or oxygen at the ambient environment or under the supercritical state. In 2012, Aryanpour et al developed the first set of ReaxFF parameters for iron (Fe)–oxyhydroxide systems based on density functional theory calculations and the parameter set has been widely applied in subsequent ReaxFF studies. Pan et al , studied the process of iron oxidation under a typical moist condition and reported that a triplex structure was formed at the end of a three-stage oxidation process to reduce the overall oxidation speed.…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al , studied the process of iron oxidation under a typical moist condition and reported that a triplex structure was formed at the end of a three-stage oxidation process to reduce the overall oxidation speed. Aral et al , investigated the effect of oxidation on the deformation of iron nanowires, and in their ReaxFF MD simulations, the iron nanowires were rapidly surface-oxidized in the atmosphere of either O 2 or H 2 O. DorMohammadi et al studied the initial stages of iron corrosion in pure water and reported the critical stages of the iron corrosion process identified as dissociation of water to OH – and H + , adsorption of OH – on the iron surface, penetration of oxygen into iron to form iron oxides, and dissolution of iron into solution. In 2015, Assowe et al developed a set of ReaxFF parameters for the nickel (Ni)–oxyhydroxide system, simulated the reaction of Ni in aqueous solution at room temperature (300 K) with an external electric field, and reported the generation of Ni composite on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Surface oxidation occurs readily as reactive metallic pristine materials are exposed to a variety of different reactive oxidizer environments. [1][2][3][4][5][6][7] As a consequence of the oxidation process, the inevitable formation of a continuous oxide shell layer naturally covers the free surface of metallic reactive materials, depending mostly on the elapsed time, the oxygen pressure, and the temperature of the environment during manufacturing, processing, and working conditions. [1][2][3][4][5][6][7] Thereby, physical, chemical, electronic, and mechanical properties of metallic nanomaterials are modified by the oxidation at the free surface.…”
Section: Introductionmentioning
confidence: 99%